Trabzon şehrinde nüfusun gelişimi ve mekânsal dağılışı - SİYAVUŞ, AHMET EMRAH (My University, 2022)
Belirli bir mekân ve zaman dilimindeki insan sayısını ifade eden nüfus, Ģehirlerin mekânsal geliĢimini doğrudan etkileyen bir dinamizmdir. ġehirlerde nüfusun artmasına bağlı olarak konut ihtiyacı artmakta, bu da Ģehirlerin yatay ve dikey yönde büyümesini hızlandırmaktadır. ġehirleĢme olarak bilinen bu süreçte nüfusun zamansal ve mekânsal değiĢiminin bilinmesi büyük önem arz eder. Bir Ģehrin nüfusu incelenirken, zaman içerisindeki geliĢimi ve değiĢimi, mekânsal dağılıĢı ve ĢehirleĢme üzerindeki etkileri ele alınır. Bu bağlamda, bu çalıĢmada Karadeniz Bölgesinin Doğu Karadeniz Bölümü‟nde yer alan Trabzon Ģehrinde nüfusun zamansal ve mekânsal değiĢimi ele alınmıĢtır. Mahallelere göre nüfusun dağılıĢ ve yoğunluğu görsel olarak ifade edilmiĢtir. Trabzon nüfusu, Cumhuriyet öncesi ve sonrası olmak üzere iki ana baĢlık altında incelenmiĢtir. ġehrin Cumhuriyet‟ten önceki nüfusu konuyla ilgili yazılmıĢ kaynaklardan elde edilmiĢ; Cumhuriyet sonrası nüfusu Türkiye Ġstatistik Kurumu‟ndan (TÜĠK) temin edilmiĢtir. Elde edilen veriler coğrafi bakıĢ açısı ile analiz edilerek harita, tablo ve grafiklere dönüĢtürülmüĢ, nüfusun geliĢimi ve mekânsal dağılıĢı ortaya konulmuĢtur.

Population, which expresses the number of people in a certain place and period, is a dynamism that directly affects the spatial development of cities. Due to the increase in population in cities, the need for housing increases, accelerating the horizontal and vertical growth of cities. In this process known as urbanization, it is of great importance to understand the temporal and spatial changes of the population. While examining a city's population, its development and change over time, its spatial distribution, and its effects on urbanization are discussed. In the context of this study, the temporal and spatial evolution of the population in the city of Trabzon, which is located in the Eastern Black Sea Part of the Black Sea Region, is discussed. The distribution and density of the population according to the neighbourhoods are expressed visually. The population of Trabzon has been examined under two main headings, before and after the Republic. For this purpose, it was obtained from the sources written on the subject in the period before the Republic; The post-republic population was obtained from the Turkish Statistical Institute (TUIK). The data obtained were analyzed from a geographical point of view and transformed into maps, tables, and graphics, and the development and spatial distribution of the population were revealed.
Population development and spatial distribution in Trabzon
Keywords: Trabzon; Population Development; Population Distribution; Nüfus GeliĢimi; Nüfus DağılıĢı